May it please the twitterverse: The use of Twitter by state high court judges. Issue 4 (2nd October 2019) - Curry, Todd A.; Fix, Michael P.
ABSTRACT: This article examines the extent to which Twitter has been adopted by judges on state supreme courts, and how these judges use the platform. While social media usage by other politicians has been examined in a variety of contexts, judges have been universally ignored. We find that elected judges are more likely to use Twitter, primarily to engage with the public. Additionally, while they do not engage with the public like traditional politicians, they increase Twitter use overall and tweet more election-related rhetoric in election years. This work extends the audiences literature in judicial politics to extra-judicial behavior of judges.